SEPARATION AND IDENTIFICATION OF NORMAL HYDROCARBON, NONADECANE IN THE CABBAGE VEGETABLES SAMPLES (Brassica oleracea VAR. CAPITATA F. ALBA) BY GAS CHROMATOGRAPHY–MASS SPECTROMETRY - M. Amzad Hossain; S. M. Salehuddin; M. J. Kabir (Indonesian Journal of Chemistry, 2008)
Toxic normal hydrocarbon (NH), nonadecane in the methanolic extract of the whole of cabbage samples collected from different districts of Bangladesh was analyzed by GC-MS. It was observed that NH deposition on the samples takes place in different morphological parts of the biological materials. The NH, nonadecane, was found in the cabbage samples collected from the highway road side by the extraction of methanol. The identification and quantification of the title compounds have not been reported previously in the cabbage sample.